Evaluation of Patients Hospitalized from the Emergency Department with Pyelonephritis - Sibel Bakırçivi; Mustafa Burak Sayhan; Ömer Salt; Aykut Yucal (Global Emergency and Critical Care)
Objective: We aimed to evaluate the demographic, etiologic, and clinical characteristics, complicating factors, laboratory and radiodiagnostic evaluations, treatment practices, and follow-up processes of hospitalized patients diagnosed with acute pyelonephritis (APN). Materials and Methods: The files of 241 patients diagnosed with APN in the emergency department and admitted to clinics in our center between May 1, 2012, and May 1, 2016, were accessed through the automation information system of our hospital. Demographic characteristics, seasonal distribution, complaints, clinical findings, laboratory tests and imaging results, treatment, follow-up, and outcome status of the patients were retrospectively scanned and evaluated. Results: The mean age of the patients was 66.00±19.61 years. 54.4% were women. The most common presenting complaints were fever and flank pain; physical examination finding was suprapubic tenderness; predisposing factor was urinary catheterization; and comorbid diseases were chronic renal failure and DM. The most common causative agent was Escherichia coli The most common imaging findings were hydronephrosis and urolithiasis. The duration of hospitalization was 10.81±7.09 days; 1.2% of patients died. Conclusion: The most common predisposing factors for the development of APN were recent antibiotic use, particularly in the last two weeks, history of hospitalization in the last two weeks, chronic renal failure, and diabetes mellitus. APN may present as a spectrum ranging from mild to urosepsis.